A Security Wireless Monitoring and Automatic Protection System for CCEL. (15th May 2021) - Sun, Qiao-yan; Liu, Xue-jiao; Sun, Yu-mei; Wang, Mei-chun; Han, Xiang; Chen, Xiang-guang
Abstract : A wireless monitoring and automatic protection system for laboratory safety is proposed to solve the security problems in chemistry and chemical engineering laboratories (CCEL). The system is based on a wireless sensor network (WSN), including indoor wireless security monitoring node, information aggregation and management node, portable handheld terminal, and laboratory security information management system. Each indoor safety wireless monitoring node can monitor the laboratory security information (for example, fire information, toxic gas content, abnormal sound in chemistry, and chemical engineering laboratory) and control the corresponding protection device. The portable handheld terminal can remind the safety responsible person to check the safety status of the laboratory remotely and can issue corresponding operation and control instructions. According to the instructions it sends, the indoor security wireless monitoring and control node can start the corresponding automatic protection device. The experimental results demonstrate that the system can realize all-weather online monitoring of indoor safety information, ensuring that some important scientific research experiments can be conducted continuously and safely, significantly reduced the workload of laboratory managers, and precisely reported the location and conditions of accidents; the loss caused by the accident can be minimized based on the automatic protection device. The system can also be used in dangerous goods warehouse and inflammable and explosive places.